2022
DOI: 10.1007/s10120-021-01275-5
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cancer-associated fibroblasts and immune cells in peritoneal metastasis: inhibition in the migration of M2 macrophages and mast cells by Tranilast

Abstract: Background The role of tumor–stroma interactions in tumor immune microenvironment (TME) is attracting attention. We have previously reported that cancer-associated fibroblasts (CAFs) contribute to the progression of peritoneal metastasis (PM) in gastric cancer (GC), and M2 macrophages and mast cells also contribute to TME of PM. To elucidate the role of CAFs in TME, we established an immunocompetent mouse PM model with fibrosis, which reflects clinical features of TME. However, the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Immunofluorescence was performed as described in a previous study. 18 Briefly, slides with the samples were incubated with CD36 antibody (NB400-144, rabbit, diluted 1:300, Novus Biologicals, Littleton, CO, USA) overnight at 4 °C. Immunoreactivity was visualized using anti-rabbit immunoglobulin (Ig) G secondary antibody conjugated with Alexa Fluor ® 546 (1:400; Molecular Probes/Invitrogen, Eugene, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescence was performed as described in a previous study. 18 Briefly, slides with the samples were incubated with CD36 antibody (NB400-144, rabbit, diluted 1:300, Novus Biologicals, Littleton, CO, USA) overnight at 4 °C. Immunoreactivity was visualized using anti-rabbit immunoglobulin (Ig) G secondary antibody conjugated with Alexa Fluor ® 546 (1:400; Molecular Probes/Invitrogen, Eugene, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed according to a previously reported standard protocol. 18 The CD36 SR-B3 antibody (NB400-144, rabbit polyclonal IgG, diluted…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse models of peritoneal tumors, CXCL12 from CAFs was suppressed. This reduced mast cell migration and degranulation and reduced tumor fibrosis [ 104 ]. Natural killer (NK) cells, an important immune component responsible for eliminating tumor cells, interact with CAFs as tumors progress.…”
Section: Cafs Modulate Immune Cell Recruitment Leading To Suppressed ...mentioning
confidence: 99%
“…Studies have shown that the antiallergic drug Tranilast can inhibit the secretory function of fibroblasts in peritoneal metastatic GC tissue, effectively improve the tumor microenvironment, increase the infiltration of CD8 + T cells, as well as reduce the infiltration of M2 macrophages and mast cells. This leads to reduced proliferation and fibrosis of GC cells ( 141 ). Futibatinib is a novel FGFR1-4 inhibitor that exhibits broad-spectrum antitumor effects in various tumors, including gastric cancer ( 142 ).…”
Section: Immunotolerance Targeting Therapies In Gcmentioning
confidence: 99%